Multi-Period Evacuation Shelter Selection considering Dynamic Hazards Assessment - M. F.N. Maghfiroh; S. Hanaoka (Faculty of Engineering and Technology, Sampoerna University, 2019)
Natural phenomena may lead to a huge disaster that is affected by triggering phenomenon and the following phenomena that occured afterward. Nevertheless, following single scenario of disaster to create a disaster emergency plan might lead to an incomparable estimation of risk. The decision maker could reduce the risk and perform an efficient evacuation, By understanding disaster prone area based on hazard assessment. This study proposed a multi-period shelter selection and relocation by considering possible impact due to cascading effect and secondary disaster. The objective was to minimize the cost associated with transport and relocation shelter during the evacuation process. A simple yet powerful Simulated Annealing was proposed to solve the model. This study compared the cost that occurred based on two approaches, hazard assessment map, and radius based map. The result showed that model with hazard map generated a better result in comparison with radius based map. Hazard map could offer different subsets of the shelters identified in the first stage to be selected, thereby producing a minimum number of evacuees.